2019
DOI: 10.3847/1538-4357/ab095b
|View full text |Cite
|
Sign up to set email alerts
|

Inferred Evidence for Dark Matter Kinematic Substructure with SDSS–Gaia

Abstract: We use the distribution of accreted stars in Sloan Digital Sky Survey-Gaia DR2 to demonstrate that a nontrivial fraction of the dark matter halo within galactocentric radii of 7.5-10 kpc and > | | z 2.5 kpc is in substructure and thus may not be in equilibrium. Using a mixture likelihood analysis, we separate the contributions of an old, isotropic stellar halo and a younger anisotropic population. The latter dominates and is uniform within the region studied. It can be explained as the tidal debris of a disrup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 99 publications
8
140
0
Order By: Relevance
“…For example, Vincenzo et al (2019) model the chemical evolution of the GS candidate stars as selected using the APOGEE and GDR2 data-sets, and find a total stellar mass at the time of the merger of order of ∼ 10 9 M , with the bulk of the dwarf's stars forming more than 10 Gyr ago. The presence of the GS merger debris was also revealed through a careful analysis of the local halo sample (Necib et al 2019b) and traced far beyond the Solar neighborhood (Lancaster et al 2019;Bird et al 2019). Deason et al (2018) connect the orbital properties of the local Main Sequence stars and the distant Blue Horizontal Branch stars and show that the two samples have very similar apo-centric distance, thus establishing that the local and the far-field halo tracers likely share a common progenitor.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Vincenzo et al (2019) model the chemical evolution of the GS candidate stars as selected using the APOGEE and GDR2 data-sets, and find a total stellar mass at the time of the merger of order of ∼ 10 9 M , with the bulk of the dwarf's stars forming more than 10 Gyr ago. The presence of the GS merger debris was also revealed through a careful analysis of the local halo sample (Necib et al 2019b) and traced far beyond the Solar neighborhood (Lancaster et al 2019;Bird et al 2019). Deason et al (2018) connect the orbital properties of the local Main Sequence stars and the distant Blue Horizontal Branch stars and show that the two samples have very similar apo-centric distance, thus establishing that the local and the far-field halo tracers likely share a common progenitor.…”
Section: Introductionmentioning
confidence: 98%
“…The standard halo model (SHM), in which the velocities of the DM particles follow an isotropic Maxwellian distribution, has commonly been used in the computation of DM direct detection rates. Recent work, however, has shown that the Milky Way's history has been punctuated by mergers with dwarf galaxies, which resulted in a rich variety of stellar substructure beyond the traditional halo and disk, such as the debris flow of the Gaia Sausage (also called Enceladus) [16,17], the Nyx stream [18,19], or the so-called "shards," the S1, S2a, and S2b streams [20][21][22]. 1 Since dwarf galaxies also contain DM, these mergers could also result in associated dark matter substructure within our galaxy, beyond that of what pertains to the SHM.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SHM, we will also consider the halo and Sausage distributions as inferred in Refs. [16,17]. Indeed, there seems to be good evidence that low-metallicity stars originating from older mergers, such as those in the Gaia Sausage, are good kinematic tracers of DM and thus allow for their associated DM distribution to be determined up to uncertainties in the substructure fraction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [31] used the SDSS-Gaia DR2 data set for a subsample of ∼ 190, 000 stars to make the first empirical determination of the local DM velocity distribution. They performed a Gaussian mixture model (GMM) analysis on the joint distribution of stellar velocities and metallicities to classify stars in three populations with distinct kinematic properties: metal-rich young disk stars formed in-situ; accreted stars which include metal-poor stars in the smooth isotropic halo, and intermediate metallicity stars with a high radial anisotropy that constitute the Gaia-Sausage substructure.…”
Section: B Dm Velocity Distributionmentioning
confidence: 99%
“…While the full implication of stellar data for the astrophysical properties of DM will take decades to analyse, pioneering work by ref. [31] used a mixture model analysis to characterize the local DM velocity distribution. They used the kinematics of MW halo stars in the cross-matched Sloan Digital Sky Survey (SDSS)-Gaia data set as tracers for the DM velocity, and validated their analysis [32] with the Fire-2 cosmological zoom-in simulation.…”
Section: Introductionmentioning
confidence: 99%